Structural investigations of the RNA-binding properties of STAR proteins. (11th August 2014) - Feracci, Mikael; Foot, Jaelle; Dominguez, Cyril
Abstract : STAR (signal transduction and activation of RNA) proteins are a family of RNA-binding proteins that regulate post-transcriptional gene regulation events at various levels, such as pre-mRNA alternative splicing, RNA export, translation and stability. Most of these proteins are regulated by signalling pathways through post-translational modifications, such as phosphorylation and arginine methylation. These proteins share a highly conserved RNA-binding domain, denoted STAR domain. Structural investigations of this STAR domain in complex with RNA have highlighted how a subset of STAR proteins specifically recognizes its RNA targets. The present review focuses on the structural basis of RNA recognition by this family of proteins.